Pengaruh Kepercayan Diri, Pendidikan Agama Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa Kelas Xi IPS Sma Negeri 1 Padangsidimpuan - Replita, Replita; Hardana, Ali (Institute Agama Islam Tafaqquh Fiddin Dumai, 2023)
The purpose of this study was to determine whether there is an effect of self-confidence, local culture and religious education on the learning outcomes of economic subjects of students in class XI IPS SMA Negeri 1 Padangsidimpuan. religious education on the learning outcomes of economic subjects of XI social studies class students of SMA Negeri 1 Padangsidimpuan both simultaneously and partially. The population of all students of class XI social studies SMA Negeri 1 Padangsidimpuan amounted to 62 students, all of whom were used as respondents. Data collection techniques data collection techniques using questionnaires and documentation. Data analysis method used is descriptive analysis technique. descriptive analysis techniques. The analysis method used is multiple regression analysis. Descriptive analysis of self-confidence students are good, local culture is very good, religious education is good. The results of this study statistically show there is an influence of self-confidence, local culture, religious education on students' economic learning outcomes. (37.7%).(2) There is an influence of self-confidence on the learning outcomes of students' economic subjects (16.56%).(3) There is an influence of local culture on the learning outcomes of students' economic subjects (10.50%).(4)There is no There is no effect of religious education on the learning outcomes of students' economic subjects.